Islamic Law, Secular Law, and Societal Norms: The Recognition of Islamic Legal Practices in the Netherlands and the Protection of Muslim Women's Human Rights. Issue 2 (2nd April 2016) - De Kroon, Eefje
Abstract: This article examines the extent to which Islamic law is accommodated in the Netherlands, by analysing legislation, case law, and the political discourse in the field of Islamic divorce, and focuses on the tension and proposed balance between gender equality and freedom of religion. It finds that, as the priority lies with protecting Muslim women's rights, Muslim law in the Netherlands remains in the unofficial sphere, potentially alienating Muslim communities. This article explores whether and how Dutch law could continue to ensure respect for gender equality while working towards greater respect for a minority group's cultural and religious freedom. Two options are presented in this regard: more responsibilities for Civil and Criminal courts, or the establishment of Sharia Councils. Lessons are drawn from the United Kingdom's experiences.